Peran Mediasi Literasi Keuangan terhadap Digitalisasi, Perilaku Konsumtif, dan Stabilitas Keuangan pada K-popers Gen Z - Tikollah, M. Ridwan; Majiding, Nurul Chalisa; Fadli, Syahir; Sahade, Sahade (Universitas 17 Agustus 1945 Jakarta, 2025)
Generation Z (Gen Z) is a consumer group whose financial behavior is strongly shaped by digitalization and cultural influences, particularly K-Pop fandom. As digital natives, Gen Z actively uses digital financial services but is also vulnerable to impulsive consumption. This study investigates the mediating role of financial literacy in the relationship between digitalization, consumptive behavior, and financial stability among Gen Z K-Pop fans in Makassar, Indonesia. Using a quantitative explanatory design, data were collected from 100 respondents aged 18–25 years who actively participate in K-Pop fandom activities and conduct digital transactions such as e-wallet usage, online shopping, or concert ticket purchases. Data analysis employed multiple regression and Sobel tests to examine mediation effects.The findings indicate that digitalization positively influences financial stability both directly and indirectly through financial literacy. Financial literacy acts as a partial mediator, strengthening the effect of digitalization on financial stability. In contrast, consumptive behavior does not significantly affect either financial literacy or financial stability. These results underscore the critical role of financial literacy in enabling Gen Z to maintain financial resilience despite the pressures of digital consumption and fandom-driven spending. This research contributes theoretically by integrating perspectives from digital finance, consumer behavior, and financial literacy within a cultural context. Practically, the findings offer insights for educators, policymakers, and financial institutions to design targeted financial literacy programs tailored to the needs of young consumers. Such interventions are essential to foster responsible financial behavior and ensure long-term financial stability in the digital era.